Schule Oberhuber - der Künstler, Rektor, Ausstellungsmacher und sein Programm - Rainer, Cosima 1969-; Stadler, Eva Maria 1964- (Edition Angewandte, 2023)
Oswald Oberhuber: A portrait This publication reveals for the first time in depth the multifaceted artistic practice of Oswald Oberhuber (1931-2020), who shaped the University of Applied Arts Vienna from the 1970s to the 1990s and initiated a discourse on the politics of art that is still relevant today. Based on the Schule Oberhuber [Oberhuber School] exhibition (University Gallery Heiligenkreuzerhof, 2022), the book addresses Oberhuber's critique of Austria's conservative postwar canon and the institutional framework for the production of art. The book situates Oberhuber's artistic position in an international context and clarifies his cultural-political, reform-oriented understanding of art education. Works by contemporary artists and students show that it is still worthwhile engaging with the collection initiated by Oberhuber and the university archive. Situates Oberhuber's work in an international context; on the history of the university's collection Documentation of the exhibition Schule Oberhuber (2022) With contributions by Bazon Brock, Julienne Lorz, Oswald Oberhuber, Thomas Trummer, et al